2021
DOI: 10.3390/life11020153
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Cellular Senescence Stress Response in Mitotically Active Brain Cells—Implications for Cancer and Neurodegeneration

Abstract: Cellular stress responses influence cell fate decisions. Apoptosis and proliferation represent opposing reactions to cellular stress or damage and may influence distinct health outcomes. Clinical and epidemiological studies consistently report inverse comorbidities between age-associated neurodegenerative diseases and cancer. This review discusses how one particular stress response, cellular senescence, may contribute to this inverse correlation. In mitotically competent cells, senescence is favorable over unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 208 publications
(209 reference statements)
0
17
0
Order By: Relevance
“…According to our results, these shared altered pathways are likely circadian regulated. These commonly altered mechanisms include malfunctions in several processes including redox homeostasis, functioning of immune system, cell cycle, DNA repair and circadian regulation [ 3 , 6 , 13 , 14 ]. Our analysis shows that upon perturbation of core-clock genes, the rhythmicity pattern of genes involved in such processes was altered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to our results, these shared altered pathways are likely circadian regulated. These commonly altered mechanisms include malfunctions in several processes including redox homeostasis, functioning of immune system, cell cycle, DNA repair and circadian regulation [ 3 , 6 , 13 , 14 ]. Our analysis shows that upon perturbation of core-clock genes, the rhythmicity pattern of genes involved in such processes was altered.…”
Section: Discussionmentioning
confidence: 99%
“…The hallmarks of physiologic aging and neurodegeneration include genomic instability, telomere attrition, epigenetic alterations, loss of proteostasis, deregulated nutrient sensing, mitochondrial dysfunction, cellular senescence, stem cell exhaustion, and altered intercellular communication [ 11 , 12 ]. Many of these processes are also relevant to tumorigenesis [ 3 , 6 , 13 , 14 ]. Genetic forms of PD are particularly interesting in this overlap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has important implications for the fields of aging and neurodegenerative disease. Senescent cells contribute to a wide range of normal and pathological changes with aging 30,31 , and are increasingly thought to play a role in neurodegenerative disease 32,33 . Sex differences in p16 and p21 expression in aged mice in vivo have been reported, although this study actually found higher levels of these in male mice than female mice 34 .…”
Section: Discussionmentioning
confidence: 99%
“…When cells are exposed to oxidative stress and/or DNA damage as a result of physical or chemical agents, premature senescence occurs [ 10 ]. Senescent cells are characterized by cell cycle arrest, resistance to apoptosis, chromatin remodeling, morphological changes, such as flattened shape, cell enlargement, and a disrupted nuclear membrane [ 11 , 12 ]. These cells have a senescence-associated secretory phenotype (SASP) which influences surrounding cells and tissues [ 13 , 14 ].…”
Section: Aging and Senescencementioning
confidence: 99%